Discovery of Comarum palustre L. (Rosaceae) in Iranian alpine refugia highlights conservation needs of mountain wetlands - Khorasani, Mina; Talebi, Amir; Djamali, Morteza; Naqinezhad, Alireza (Phytotaxa, 2026)
Comarum palustre, a circumpolar boreo-temperate helophytic species of the monotypic genus, is recorded here for the first time from continental Southwest Asia (Iranian Plateau). The species was collected from a peat bog developed within Lake Almalou, a volcanic crater lake situated in the northwest of Iran. Despite extensive explorations of wetlands and mire vegetation across Iran, no other populations of C. palustre have been detected, underlining its extreme rarity in the region. The discovery of this species in an isolated wetland at the southernmost edge of its distribution range highlights the role of Quaternary climatic oscillations in shaping its distribution, as well as the importance of such interglacial refugia for conserving isolated populations of cold-adapted plant species in low-latitude mountain systems. This finding underscores the need for careful taxonomic work in low-latitude biodiversity hotspots to uncover hidden diversity and to inform conservation of vulnerable aquatic ecosystems. A comprehensive description, with taxonomic and ecological notes, illustrations, and a conservation assessment following IUCN guidelines, is provided. Furthermore, distribution maps of C. palustre are also presented here, along with key differences from its closest relative.